Development of Personalized Travel Products for Smart Tour Guidance Services - Woo Jwa, Jeong; ., . (International Journal of Engineering and Technology, 2018)
Smart tourism is the application of the key technologies of the 4th industrial revolution. This research proposes a smart tourism system to develop the personalized travel products for smart tour guidance services. The proposed smart tourism system consists of a smart tourism app and a smart tourism server. Adobe XD is used to UI/UX design of the android based smart tourism app. The smart tourism server provides the recommend travel products to FITs before or during the trip. FITs can create the personalized travel product using the chosen recommend travel products, tour information such as tourist attractions, lodgments, and restaurants. During the trip, FITs can use smart tour guidance services according to the tour schedule in the personalized travel product. In the developed smart tourism system, FITs can modify the personalized travel product during their trips and register them as the recommend travel products after their trips.Â Â